Determination of Nasab of Children Outside of Marriage in the Islamic Legal System: The Role and Decisions of Religious Courts in Indonesia - Syukriya Husni; Fadilla Syahriani; Alfi Husni; Annisa Wahid; Valensius Ngardi (Yayasan Lembaga Studi Makwa, 2024)
The determination of nasab for children born outside of marriage is a multifaceted legal and social issue, especially within the context of family law in Indonesia. This study delves into the critical role and decisions of Religious Courts in Indonesia concerning the nasab of such children, exploring how these courts balance national legal frameworks with the principles of Islamic law. Through a comprehensive analysis, the study highlights the legal factors, justifications, and ratio decidendi that underpin the decisions of the Religious Courts. It is imperative to understand the methodologies these courts employ in interpreting legal precedents, applying Islamic jurisprudence, and considering the broader social implications of their rulings. The investigation also looks into the procedural aspects of these cases, including the presentation of evidence, the involvement of legal and religious experts, and the impact of societal norms and pressures on judicial outcomes. It explores how the rulings influence public perceptions of legitimacy, inheritance rights, and social status, as well as their impact on the lives of children born outside of marriage and their families. The findings of this study underscore the dynamic interplay between religious norms and legal requirements in Indonesia, highlighting the challenges and opportunities in harmonizing these two systems. The study concludes by emphasizing the necessity for ongoing research to evaluate the long-term effects of these rulings on children's rights, social cohesion, and the development of a more inclusive and just legal framework.